An industrial quality control study On Toyota Boshoku Philippines Corporation - Dizon, Charity; Patawaran, Ma. Rizza; Villamil, Isabela (Diliman, Quezon City College of Engineering, 2006)
Toyota Boshoku Philippines Corporation (TBPC) is an auto interior parts manufacturer in the Philippines. It is a subsidiary company of Toyota Motors Japan and was established on March 6, 1996. TBPC is 100 percent owned by Toyota Corporation in Japan. The company engages in the manufacturing of automotive interior parts, particularly seat, door trim and PU Foam assembly for various models of line with the production demand of Toyota Motors Philippines, TBPC produces components for three car models: Innova, Corolla Altis, and Camry. This study was limited to the Toyota Innova (IMV) because of its high demand due to its recent introduction in the Philippine Market. The study focused on applying Statistical Process Control, total quality management concepts, and other quality control tools on TBPC's seat assembly for the Toyota Innova. The purpose was to create a balance between quality and production costs through statistically proven methods and to evaluate this with respect to the quality system as a whole, and moreover to produce car parts in line with the Innova's goal of stability, safety, space, and comfort. Data from January to July was provided by the management of TBPC and these were sorted according to the three sub-assemblies plus the seat assembly line. Information regarding the company profile, process, product, quality system were collected and evaluated. Problem areas were then identified through observation, analysis of the system documented, and by recommendations of the company itself. Statistical Process Control was used to assess the data given. Control charts, hypothesis testing and other applicable tools were applied to the given data. The different attributes data were studied and the corresponding control charts made. Problem identification tools such as the Ishikawa diagram were used -- analyses and recommendations center on these. Quality and environmental policies, and other aspects of the system were also briefly examined and are discussed in the implementing steps. An initial look at the total productivity index of TBPC for the last few months show that it is decreasing. This is a good sign because it shows that the production times are reaching and even overcoming the standard times. In addition, a look at the total product rejection and delivery rejection charts show that TBPC has a minimal rejection rate. This information combined with the previous one shows that TBPC's performance is positive. However, a more in depth look shows that TBPC still hasn't reached the policy of Toyota Motors Company of a rejection of fifteen parts per million. It was determined that most of the problems that arise during production are due to human limitations. Human error plays a big part in the rejection rates. It is recommended that additional reminders on the proper production processes should be instituted by the individual line managers either by memos or by short meetings before or after the work shift. Aside from this, a comprehensive review of the kanban cards (which contain the process) and check sheets should be done by everybody involved in production. For incapable processes, it is highly recommended to utilize powerful techniques such as design of experiments (DoE) or Taguchi. These techniques are very useful for minimizing or even elimination common causes of variation from the process. When changes or modifications are made to a process either to improve a sub-process or the whole process, it is important that they are noted and documented. Management should institute policies so as to ensure that knowledge of any critical processes is reviewed, documented and updated as the process changes. It is essential that these encountered situations are documented and fed forward in order that there is knowledge of what to do when a similar situation would arise in the future. Once SPC has been successfully implemented to one process, it is then much easier to extend its applications to other processes within the organization. After performing these techniques, it is strongly encouraged that TBPC evaluate the potential benefits in financial terms. This would provide a wider acceptance and appreciation of the power of such practices among top management and employees with the organization.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Toyota Boshoku Philippines Corporation; Automobile industry and trade; Quality Control